EVALUATION OF THE INFLUENCE OF MOTOR DISORDERS ON THE QUALITY OF LIFE OF PATIENTS WITH COMOBIDITY OF PARKINSON'S DISEASE AND FRAILTY AND THE EFFICIENCY OF THEIR CORRECTION BY PHYSICAL THERAPY - I.V. Didoha (Клінічна та профілактична медицина, 2021)
Summary. Purpose of the study: to assess the effect of motor disorders on the quality of life of elderly patients with comobility of Parkinson's disease and frailty and to evaluate the effectiveness of their correction by means of physical therapy.